2015
DOI: 10.1007/s00415-015-7954-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor short-term outcome in patients with ischaemic stroke and active cancer

Abstract: Stroke risk is increased in cancer patients and cancer activity has been claimed to play a role in the development of ischaemic stroke (IS). We wanted to further test these assumptions and to explore the impact of such relation on short-term prognosis. We identified all IS patients that were admitted to the neurological department of our primary and tertiary care university hospital between 2008 and 2014 (n = 4918) and reviewed their medical records for an additional diagnosis of cancer. Cancer patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 26 publications
10
113
1
1
Order By: Relevance
“…13 Furthermore, cancer patients with stroke generally have worse discharge disposition and are more likely to develop early neurological deterioration and in-hospital death than non-cancer patients with stroke. 13, 14 In a case-control study, 32% of cancer patients with ischemic stroke had in-hospital death versus 13% of non-cancer patients with ischemic stroke. 37 Small retrospective studies have reported that high D-dimer levels may be predictive of early neurological deterioration and death in cancer-associated stroke.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…13 Furthermore, cancer patients with stroke generally have worse discharge disposition and are more likely to develop early neurological deterioration and in-hospital death than non-cancer patients with stroke. 13, 14 In a case-control study, 32% of cancer patients with ischemic stroke had in-hospital death versus 13% of non-cancer patients with ischemic stroke. 37 Small retrospective studies have reported that high D-dimer levels may be predictive of early neurological deterioration and death in cancer-associated stroke.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…During 1994–2011, approximately 40% of stroke patients in Denmark had major comorbidities at diagnosis, and this proportion has increased in recent years . Comorbidity affects both short‐ and long‐term mortality after hospital admission for stroke. However, it is unknown whether comorbidity leads to excess post‐stroke mortality, that is mortality beyond that expected from combined individual effects of stroke and comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It' s a remarkable that the rate of cancer incidence is higher among ischemic stroke patients than the general population 9,13,21,22,25) , and cancer itself may increase a risk of CI occurrence 10,11,16,30) . Once CI occurs in patients with cancer, neurological outcomes significantly worsen, and prognosis tends to be poor in addition to stroke-associated morbidity/mortality 5,15,19) . Among all cancer types, patients with lung cancer have the highest incidence of CI 4) .…”
Section: Discussionmentioning
confidence: 99%